Without a radical rethinking of the role of data, the SDGs will fail to "leave no one behind" - Johannes P. Jütting; Sasha Ramirez-Hughes (Kiel Institute for the World Economy (IfW Kiel), Poverty Reduction, Equity and Growth Network (PEGNet), 2022)
The 2030 Agenda for Sustainable Development calls on countries to report on an extensive set of indicators, aimed at ensuring that no one is 'left behind', yet today, nearly halfway towards the end, most countries are struggling to produce the required data. The COVID-19 pandemic, climate change, conflict and instability are setting back SDG progress while also making it more difficult for national statistical offices to produce data. Johannes Jütting & Sasha Ramirez-Hughes suggest in their Policy Brief to use new tools and platforms to better match supply and demand, new data sources and citizen-generated data along with the better usage of existing data that could deliver substantial benefits.
Keywords: 330